PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM BERBASIS KOMUNIKASI ISLAMI PADA REMAJA MASJID (AT-TAWASUL, 2025)
This research discusses the cultivation of Islamic education values based on Islamic communication in adolescents who are members of the mosque youth organisation, the background of the research shows the urgency of planting the existence of Islamic education values in non-formal educational institutions in the midst of society is very urgent to pay attention to. The method used in this research is descriptive qualitative, using observation and interview techniques. The results showed that increasing knowledge of the existence of Islamic education values in the Islamic education values cultivation programme can be achieved through structured learning planning, effective time distribution, the use of teaching strategies and methods that are easy to understand, grouping based on ability and age group, and periodic evaluation. The response of mosque youth members and mosque youth coaches shows a significant increase, especially in the aspect of social life which is reflected in the moral changes of mosque youth. Overall, this programme is effective in increasing the knowledge of teenagers about the importance of the existence of Islamic education values in carrying out daily life